A Semiotic Analysis of Fashion Domination through Signs in Music Videos - Erika Khairunnisa (Passage, 2014)
This paper entitled “A Semiotic Analysis of Fashion Domination through Signs in Music Videos” aims to investigate domination issues in the form of fashion by examining denotative, connotative, and mythical meanings of selected scenes in three music videos. The three music videos are Ailee’s “I Will Show You”, Taylor Swift’s “You Belong with Me”, and Super Junior M’s “Super Girl” as the representatives of Korean, American, and Chinese music videos. The orders of signification were used as the semiotic tools to analyze the data. The results show that a change of appearance emerges in the music videos as a form of domination to maintain the dominant ideology.Keywords: Fashion, Semiotic, Denotation, Connotation, Myth, and Domination